Efek Antibakteri Tumbuhan Pepaya (Carica Papaya L.) Terhadap Porpyromonas Gingivalis (Laporan Penelitian) - Meiny Faudah Amin; Taufiq Ariwibowo; Febria Febria (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: Porphyromonas gingivalis is one of the bacteria that cause pulp necrosis, NaOCl is an irrigation solution that has become the gold standard in endodontic treatment, however NaOCl is toxic, so other alternative materials are needed. One usable material is papaya plant (Carica papaya L.) which has antibacterial properties. Objective: to know the differences in the activity of papaya leaves extract, papaya seed extract, and papaya fruit juice in inhibiting P.gingivalis. Methods: This study is an in vitro experimental laboratory of agar well diffusion method used papaya seeds extract, papaya leaves extract and papaya fruit juice in several consentrations (6.25%,12.5%,25%,50%, and 100%) and NaOCl 5,25% as positive control. Results: This study showed that the diameter of inhibitory zone against P.gingivalis was found on 2 concentrations of papaya seed extract, a concentration of 100% with an average 23,43 mm and concentration of 50% with an avarege 16,43 mm. The inhibition zone test of papaya leaves extract and papaya fruit juice against P.gingivalis was not found around the well. Conclusion: Papaya seed extract was able to inhibit P.gingivalis in certain concentration, while papaya leave extract and papaya fruit juice were not able to inhibit the growth of P.gingivalis.